L'amour fou - Eloy, Jean-Claude 1938- (Radiance Films, 2024)
Die Liebes- und Ehegeschichte zwischen einem jungen Regisseur und einer Schauspielerin als Grundlage eines verschachtelt und auf komplexe Weise erzählten Films. In langen, oft ungeschnittenen Bildfolgen beobachtet die Kamera die Auseinandersetzungen des zerstrittenen Paares, die von Bildern einer Theaterprobe zu Racines "Andromaque" unterbrochen und kommentiert werden. Aus dem Geflecht aus Fiktion und Wirklichkeit ergibt sich in diesem improvisierten Film ein sehr intimes, sehr intelligentes Journal über die Beziehungen zwischen Kunst und Leben. [Film-Dienst.de]
Original: Frankreich 1969
Blu-ray limited edition special features: 4K restoration from materials kept at Les Archives du Film and in Éclair-Preservation, under the supervision of Caroline Champetier ; uncompressed mono PCM audio ; Cinema redefined: Jacques Rivette's L'amour fou revisited: a newly filmed feature-length documentary featuring new interviews with actor Jean-Pierre Kalfon; writer and Rivette collaborator Pascal Bonitzer; critics Antoine de Baecque and Sylvie Pierre; and archival footage of Jacques Rivette (Robert Fischer, 2024, 95 mins) ; new interview with Caroline Champetier, renowned cinematographer and restoration supervisor, and Audrey birrien, restoration project manager (2024, 26 mins) ; The third eye - a video essay by film critics Cristina Álvarez López and Adrian Martin (2024, 14 mins) ; trailer ; newly translated English subtitles ; reversible sleeve featuring original and newly commissioned artwork ; limited edition booklet featuring new writing by Jessica Felrice and archival writings by Véronique Manniez-Rivette, an archival interview with Jacques Rivette and images of the director’s notes
Bildformat 1.85:1
Keywords: Film; Blu-Ray-Disc